Neonatal outcomes in offspring of mothers with pregestational diabetes: a hospital-based multicentre prospective cohort study protocol - Manu Raj; Vishnu Renjith; Renjitha Bhaskaran; Anju Philip Thurkkada; Radhamany Kunjukutty; Sobha S Nair; Annie Soman; Sethulakshmi Ramachandran (BMJ Paediatrics Open)
Introduction Pregestational diabetes mellitus (PGDM) occurs when a woman becomes pregnant after having diabetes mellitus. The presence of diabetes during the entire pregnancy can have an adverse impact on fetal and neonatal outcomes. The objective of this study is to examine the association between PGDM and neonatal outcomes at birth.Methods and analysis This prospective hospital-based cohort study is ongoing at three tertiary-level hospitals in Kerala, India. The study targets to recruit 1260 pregnant women. All pregnant women above the age of eighteen who had confirmed pregnancy in an early pregnancy scan and in the first trimester of pregnancy visiting the three study sites for antenatal care will be included in the study. Those who will have a miscarriage, an abortion or twin pregnancies will be excluded from the study. All pregnant women will be evaluated for diabetic state via RBS, HbA1c and FBS based on the International Association of Diabetes and Pregnancy Study Groups criteria during their initial visit to the study sites. PGDM will be diagnosed by the following criteria—FBS ≥126 mg% OR HbA1c ≥6.5 mg% OR Random blood glucose ≥200 mg% on the initial visit or documented prior to the index pregnancy. Neonatal outcomes among the newborn babies will be assessed on the day of birth. We will report adjusted ORs with 95% CI for significant associations derived from multivariable logistic regression analysis.Ethics and dissemination The present study received ethical approval from the three study sites. Informed consent will be obtained from the study participants before data collection.Trial registration number CTRI/2024/06/068978.Conclusion Early identification and management of PGDM among mothers will probably help to prevent adverse neonatal outcomes at birth.